The Pipeline Repertoire for Ig-Seq Analysis - López-Santibáñez-Jácome, Laura; Avendaño-Vázquez, S. Eréndira; Flores-Jasso, Carlos Fabián (Frontiers in Immunology, 2019)
With the advent of high-throughput sequencing of immunoglobulins (Ig-Seq), the understanding of antibody repertoires and its dynamics among individuals and populations has become and exiting area of research. There are an increasing number of computational tools that aid in every step of the immune repertoire characterization. However, since not all tools function identically, every pipeline has its unique rationale and capabilities, creating a rich blend of useful features that may appear intimidating for newcomer laboratories with the desire to plunge into immune repertoire analysis to expand and improve their research; hence, all pipeline strengths and differences may not seem evident. In this review we provide an organized list of the current set of computational tools, focusing on their most attractive features and differences in order to carry out the characterization of antibody repertoires so that the reader better decides a strategic approach for the experimental design, and computational analyses of immune repertoires.